Cover, Content, and Editorial Note from Borneo J Pharm Vol. 3 No. 4 November 2020 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2020)
Alhamdulillahirabbil ‘Alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published in November 2020. Starting from this edition, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve the circulation of the best articles published by Borneo J Pharm. Also, starting from this edition, Borneo J Pharm applying the publish-as-you-go issue to present the title of the article that has been received as early as possible in order to increase the chances of readability and quotation of articles in Borneo J Pharm. This edition contains ten articles consisting of Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, Clinical-Community Pharmacy, and Management Pharmacy. This edition includes writings from four countries including Indonesia, India, Malaysia, and Sudan. The authors come from several institutions, including Indubhai Patel College of Pharmacy and Research Center, SAL Institute of Pharmacy, Universitas Lambung Mangkurat, Badan Penelitian dan Pengembangan Kebun Raya Banua Kalimantan Selatan, Universitas Kristen Krida Wacana, University of Gezira, International Islamic University Malaysia, Universitas Mandala Waluya, Universitas Islam Bandung, Universitas Halu Oleo, Universitas Garut, Universitas Bali Internasional, and Akademi Farmasi Surabaya. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for publication in the next edition in February 2021.